The acute toxic effects of platinum nanoparticles on ion channels, transmembrane potentials of cardiomyocytes in vitro and heart rhythm in vivo in mice - Lin CX (Dove Medical Press, 2019)
Cai-Xia Lin,1,2 Jing-Li Gu,2 Ji-Min Cao11Key Laboratory of Cellular Physiology (Shanxi Medical University), Ministry of Education, Department of Physiology, Shanxi Medical University, Taiyuan, People’s Republic of China; 2Department of Physiology, Institute of Basic Medical Sciences, Chinese Academy of Medical Sciences, School of Basic Medicine, Peking Union Medical College, Beijing, People’s Republic of ChinaBackground: Platinum nanoparticles (PtNPs) have been considered a nontoxic nanomaterial and been clinically used in cancer chemotherapy. PtNPs can also be vehicle exhausts and environmental pollutants. These situations increase the possibility of human exposure to PtNPs. However, the potential biotoxicities of PtNPs including that on cardiac electrophysiology have been poorly understood.Methods: Ion channel currents of cardiomyocytes were recorded by patch clamp. Heart rhythm was monitored by electrocardiogram recording. Morphology and characteristics of PtNPs were examined by transmission electron microscopy, dynamic light scattering and electrophoretic light scattering analyses.Results: In cultured neonatal mice ventricular cardiomyocytes, PtNPs with diameters 5 nm (PtNP-5) and 70 nm (PtNP-70) concentration-dependently (10–9, – 10–5, g/mL) depolarized the resting potentials, suppressed the depolarization of action potentials and delayed the repolarization of action potentials. At the ion channel level, PtNPs decreased the current densities of INa, IK1 and Ito channels, but did not affect the channel activity kinetics. In vivo, PtNP-5 and PtNP-70 dose-dependently (3–10 mg/kg, i.v.) decreased the heart rate and induced complete atrioventricular conduction block (AVB) at higher doses. Both PtNP-5 and PtNP-70 (10–9, – 10–5, g/mL) did not significantly increase the generation of ROS and leak of lactate dehydrogenase (LDH) from cardiomyocytes within 5 mins after exposure except that only very high PtNP-5 (10–5, g/mL) slightly increased LDH leak. The internalization of PtNP-5 and PtNP-70 did not occur within 5 mins but occurred 1 hr after exposure.Conclusion: PtNP-5 and PtNP-70 have similar acute toxic effects on cardiac electrophysiology and can induce threatening cardiac conduction block. These acute electrophysiological toxicities of PtNPs are most likely caused by a nanoscale interference of PtNPs on ion channels at the extracellular side, rather than by oxidative damage or other slower biological processes.Keywords: platinum nanoparticle, transmembrane potential, ion channel, arrhythmia, nanotoxicity, heart